ANTONYMY STRATEGY IN TRANSLATING UTTERANCES FROM ENGLISH INTO INDONESIAN IN A SERIES ENTITLED “YOUNG SHELDON” SEASON 01 EPISODES 1 - 5 - Tambunan, Sunarti Desrieny (Asosiasi Dosen Muda Indonesia, 2023)
Antonymy is a translation strategy with the oppositeness of meaning by changing the positive element in the source text into negative in the target text or the negative element in the source text into positive in the target text. This present research aims at exploring the implementation of antonymy strategy in translating utterances from English into Indonesian in a series entitled “Young Sheldon” season 1 episodes 1-5. The antonymy is based on semantic point of view. By applying qualitative research, the result shows that there are eleven (11) data found that are translated using antonymy strategy based on Chesterman (2016). The data are taken from a series entitled “Young Sheldon”, season 1 from episodes 1 until 5. Even though there is a changing, the meanings are all transferred accurately from the source text into the target text.